2012
DOI: 10.1111/j.1533-8525.2012.01245.x
|View full text |Cite
|
Sign up to set email alerts
|

Constrict in the School Context: The Impact of Ethnic School Diversity on the Quantity and Quality of Friendships

Abstract: Constrict theory states that, in the short run, ethnic diversity in any context lowers both the quantity and the quality of interpersonal contacts. We test this theory in the school context, expecting that ethnic school diversity yields fewer and lower quality friendships. Moreover, we investigate whether the associations hold when controlling for the school's socioeconomic situation, and whether the relations between ethnic school diversity and the social outcomes differ between natives and immigrants. Multil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
14
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 21 publications
(15 citation statements)
references
References 57 publications
(129 reference statements)
1
14
0
Order By: Relevance
“…Students' classroom and neighborhood diversity were not related to a smaller number of friendships. In line with our findings, Demanet et al (2012) also found that middle school diversity was not related to the number of friendships in Belgian schools, once they controlled for the schools' socioeconomic composition. Our study adds to the study of Demanet et al (2012) in two ways.…”
Section: Discussionsupporting
confidence: 91%
See 4 more Smart Citations
“…Students' classroom and neighborhood diversity were not related to a smaller number of friendships. In line with our findings, Demanet et al (2012) also found that middle school diversity was not related to the number of friendships in Belgian schools, once they controlled for the schools' socioeconomic composition. Our study adds to the study of Demanet et al (2012) in two ways.…”
Section: Discussionsupporting
confidence: 91%
“…Second, next to classroom diversity, we showed that students' neighborhood diversity did not affect the total number of friendships in school either. Demanet et al (2012) and our study focus on European middle schools only (Belgian and Dutch), so more studies are warranted, but so far we find no evidence for Putnam's constrict hypothesis in these European middle schools.…”
Section: Discussionmentioning
confidence: 61%
See 3 more Smart Citations